TRANSFORMATIONAL LEADERSHIP, INTRINSIC MOTIVATION, AND TEAMWORK AS PREDICTORS OF BUSINESS FLEXIBILITY IN CULINARY SME RESTAURANTS - Reni Hindriari; Sidik Priadana; Tete Saepudin (Yayasan Putra Adi Dharma, 2026)
The development of digital technology, market changes, and intense competition require culinary restaurant SMEs to possess high business flexibility in order to adapt quickly. However, many business owners still face challenges in innovation, decision-making, work coordination, and operational development. This study aims to analyze the influence of transformational leadership, intrinsic motivation, and teamwork on the business flexibility of culinary restaurant SMEs in the Bekasi region, West Java. The study employed a quantitative approach using an explanatory survey method through the distribution of questionnaires to culinary restaurant SME owners. Data analysis was conducted using Structural Equation Modeling (SEM) based on Lisrel. The results indicate that transformational leadership, intrinsic motivation, and teamwork have a positive and significant effect on business flexibility, both partially and simultaneously. Intrinsic motivation was found to be the most dominant factor, followed by transformational leadership and teamwork. These findings suggest that SME business flexibility can be enhanced through inspirational leadership, strengthening internal motivation, and effective teamwork collaboration.